Black Box Testing On Best Sales Selection System Application Using Equivalence Partitions Techniques - Adriyan Abdi Arbeit; Dea Ramadhanti; Rayhan Alief Rizky Akbar; Syaifu Ramadhan; Aries Saifudin (Shofanah Media Berkah, 2023)
The purpose of application testing is to verify that the program works correctly so that the created program is of high quality. The testing technique consists of Whitebox testing and Blackbox testing which are widely used by researchers. The survey software that Blackbox testing is investigating is the best sales selection system that consists of a single form that is filled out with both sales information and sales results while you are in the business. Best Sales Selection is tested by Blackbox testing, where the purpose of this test is only to see that the program is the same as the desired function of the program without using the program code used. Types of testing for different Blackbox methods, one of which is equivalent slices used by the authors in this study. The technique of Equivalent Partitions is a test based on entering the data of each form into a bestselling selection system, each menu item is tested and grouped according to activity whether it is valid or invalid. Thus, this test is expected to have the quality of the software produced according to the expected performance and can benefit the company.